2007
DOI: 10.1097/mcc.0b013e32808255c6
|View full text |Cite
|
Sign up to set email alerts
|

Neurocritical care: a distinct discipline?

Abstract: Neurocritical care is one of the newest subspecialties of medicine and is at the forefront of bringing effective new therapies to patients with life-threatening neurological diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 30 publications
0
51
0
3
Order By: Relevance
“…The relation between ICP and PI was estimated by the linear regression equation: ICP = 15.067 + 5.619 x PI, (the increase of (10,16,18,20). It has been demonstrated that waveforms obtained with TCD are affected by both increases of ICP or decreases of CPP.…”
Section: Gura M Et Al: Correlation Of Pulsatility Index With Intracrmentioning
confidence: 99%
“…The relation between ICP and PI was estimated by the linear regression equation: ICP = 15.067 + 5.619 x PI, (the increase of (10,16,18,20). It has been demonstrated that waveforms obtained with TCD are affected by both increases of ICP or decreases of CPP.…”
Section: Gura M Et Al: Correlation Of Pulsatility Index With Intracrmentioning
confidence: 99%
“…3 care. The "golden hour" after newborn delivery-a concept that is borrowed from trauma and emergency medicinerefers to the period during which prompt and appropriate supportive care, as well as transfer to a center where definitive care can be provided, will be most likely to prevent death or permanent disability.…”
Section: Resuscitation and Supportive Carementioning
confidence: 99%
“…3 Centers of excellence in the United States and abroad have adapted the principles of neurocritical care (Table 2) to reflect the needs of the developing newborn brain.…”
Section: Introductionmentioning
confidence: 99%
“…These developments have led to improved outcomes in many types of neurological injury and illness and fueled basic science and clinical research that advances patient care [187,188]. The field of pediatric neurocritical care has no doubt been stimulated by these developments.…”
Section: Pediatric Neurocritical Carementioning
confidence: 99%